2005
DOI: 10.1590/s1516-93322005000200013
|View full text |Cite
|
Sign up to set email alerts
|

Ranitidine treatment inducing methemoglobinemia in male Wistar rats

Abstract: Drug idiosyncrasy is an adverse event of unknown etiology that occurs in a small fraction of people taking a drug. The histamine-2 (H2)-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 11 publications
3
7
0
2
Order By: Relevance
“…This result may due to oxygen free radical scavenger of ranitidin and its ability to healing gastric ulcer and stopping of hemorrhage. this result is agreement with (64).…”
Section: Discussionsupporting
confidence: 92%
“…This result may due to oxygen free radical scavenger of ranitidin and its ability to healing gastric ulcer and stopping of hemorrhage. this result is agreement with (64).…”
Section: Discussionsupporting
confidence: 92%
“…The same effect was observed in human duodenal ulcers treated with 150mg of ranitidine every 12 hours for 2 weeks (Hrycek et al 1994) and in rats treated with a single dose of 100mg/kg (Malfará et al 2005). In the human study, few leukocytes were found, but they showed greater phagocytic activity than before treatment (Hrycek et al 1994).…”
Section: Discussionsupporting
confidence: 58%
“…Hemoglobin type was not determined in this study, but it has been reported that ranitidine leads to methemoglobin formation in rats, suggesting that this drug is an inductor of this process (Malfará et al 2005). If the sheep in this study had increased methemoglobin formation, it must have been small because no change in the respiratory rate or mucous membrane color of the animals was detected.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Efeitos colaterais têm sido relatados com baixa incidência e, dentre eles, casos de hepatite mista e hepatite colestática ocorrem geralmente por hipersensibilidade (BERTACCINI; SCARPIGNATO, 1982;MALFARÁ;SOUZA;QUEIROZ, 2005).…”
Section: Ranitidinaunclassified